FEMALE CULT IN THE WORLD MODEL OF THE YOUTH AMUSEMENT “ZOOHOY NAADAN” AMONG BURYATS OF CISBAIKALIA - Nikolaeva, Darima (Revista Inclusiones, 2020)
The aim of the study is to identify the female cult in the world model of the youth amusement, not only in a theoretical sense, but also in an interdisciplinary context. The problem of studying the integrity of ideas and actions seems to be relevant in the process of studying various aspects of the surrounding world conceptual comprehension. The empirical methods were used to conduct the study. Basing on them, an analysis of the interviews was made. The interviews were realized with three informants in the Alarsky district and six informants in the Nukutsky district of the Irkutsk region, aged from 80 to 90. Desk methods were also used (analysis, synthesis, interpretation). As a result of the study, it was revealed that only elderly, prosperous women, having progeny without loss, healthy, financially secure, were the organizers of youth amusement between the spouses. Therefore, during the fun of young people, they tracked potential brides and grooms, marking them with sacred food. In addition, these women were also organizers of ritual prayers and sacrifices to the spirits of nature, creating an archaic model of the world based on the mother cult in different constants: space, time, folklore, society. Thus, with the example of the youth amusement and the use of modern research methods we revealed the amazing, almost forgotten world of ancient people, who mastered and explained the laws of the Universe through the cult of the mother-progenitor.